2017
DOI: 10.1371/journal.pone.0177605
|View full text |Cite
|
Sign up to set email alerts
|

Long chain saturated and unsaturated fatty acids exert opposing effects on viability and function of GLP-1-producing cells: Mechanisms of lipotoxicity

Abstract: Background and aimFatty acids acutely stimulate GLP-1 secretion from L-cells in vivo. However, a high fat diet has been shown to reduce the density of L-cells in the mouse intestine and a positive correlation has been indicated between L-cell number and GLP-1 secretion. Thus, the mechanism of fatty acid-stimulated GLP-1 secretion, potential effects of long-term exposure to elevated levels of different fatty acid species, and underlying mechanisms are not fully understood. In the present study, we sought to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
(47 reference statements)
0
14
1
3
Order By: Relevance
“…L-cell dysfunction has been reported in the DIO models for the GLP-1 reduction 3 5 . Although LCFAs have been reported to inhibit L-cell function through induction of endoplasmic reticulum stress or cell apoptosis 23 , 24 , the mitochondrial response in the L-cell dysfunction remains unknown. Our data suggest that the L-cell dysfunction is associated with mitochondrial stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…L-cell dysfunction has been reported in the DIO models for the GLP-1 reduction 3 5 . Although LCFAs have been reported to inhibit L-cell function through induction of endoplasmic reticulum stress or cell apoptosis 23 , 24 , the mitochondrial response in the L-cell dysfunction remains unknown. Our data suggest that the L-cell dysfunction is associated with mitochondrial stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…We divided FAs into saturated FAs (SFAs) and unsaturated FAs (UFAs) because of their different biological functions. 28 In our previous study, the decrease of saturated FA content was an important lipid marker for the weakening of skin barrier function, while the increase of unsaturated FA content was an important lipid marker for the destruction of skin barrier function. 29 In addition, although the contents of glycerolphospholipids (GPs) and ceramides (Cers) did not show a trend change, it is worth noting that both GPs and Cers have a positive effect on skin barrier function.…”
Section: The a Sso Ciati On B E T Ween The Effec T Of S E X Hormone S On S Ebum And S K In Cond Iti Onmentioning
confidence: 87%
“…Importantly, when reviewing the literature, we found a lack of in vitro and in vivo studies showing the assessment of ceramide levels in response to unsaturated fatty acids such as palmitoleate or EPA/DHA. For instance, the authors of [99] used GLP-1-secreting GLUTag cells and found that PA (C16:0) but not palmitoleate (PO, C16:1) induces ceramide production, whereas unsaturated fatty acids confer lipoprotection by enhancing cell viability. Additionally, unsaturated fatty acids can ameliorate inflammation triggered by palmitate [79,100,101]; therefore, it is possible that they can decrease ceramide levels or at least reverse the effects of ceramide.…”
Section: Discussionmentioning
confidence: 99%